UDK621.034 ANALYSIS OF EMULSIONS OBTAINED IN ULTRASONIC HOMOGENIZER AND MAGNETIC STIRRER DEVICES. - Ismoilova, Muxtasar; Salikhanova, Dilnoza; Adashev, Bexzod; Muratov, Mirtoxir (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Today, the application of water-oil emulsions will help not only increase the quality indicators of the product but also reduce its cost. This is done by introducing quality products into their composition. But it is also possible to improve the cooking processes, i.e., the quality of the output product, by lubricating the molds using various emulsions.